Prevention of ventricular arrhythmia complicating acute myocardial infarction by local cardiac denervation. (1st April 2015) - Chen, Jugang; Li, Min; Yu, Yanwei; Wu, Xiuli; Jiang, Rui; Jin, Yingying; Li, Jingjie
Abstract: Background: Augmentation of sympathetic nerve activity after acute myocardial infarction (AMI) contributes to fatal arrhythmia. In this study, we investigated whether local ablation of the coronary sinus (CS) and great cardiac vein (GCV) peripheral nerves could reduce ventricular arrhythmias (VA) in a canine AMI model. Methods: Twenty-one anesthetized dogs were randomly assigned into the sham-operated, MI and MI-ablation groups, respectively. The incidence and duration of VA were monitored among different groups. The ventricular effective refractory period (ERP), the ERP dispersion and the ventricular fibrillation threshold (VFT) were measured during the experiments. Norepinephrine (NE) levels in CS blood and cardiac tissue were also detected in this study. Results: The incidence and duration of VA in MI-ablation group were significantly reduced as compared to the MI dogs (p < 0.05). Furthermore, local cardiac denervation drastically prolonged the ventricular ERP in the ischemia area, decreased the ERP dispersion, and reduced NE levels in CS blood (P < 0.05). VFT also showed an increased trend in the AMI-ablation group. Conclusions: The results of this study indicate that, in the canine AMI model, local ablation of CS and GCV peripheral nerves reduces VA occurrence and improves ventricular electrical stability with no obvious effects on heart rate, mean arterial pressure and infarct size. This study suggests that local cardiac denervation may prevent ventricular arrhythmias complicating AMI.